2016
DOI: 10.1073/pnas.1603827113
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a phleboviral envelope glycoprotein reveals a consolidated model of membrane fusion

Abstract: An emergent viral pathogen termed severe fever with thrombocytopenia syndrome virus (SFTSV) is responsible for thousands of clinical cases and associated fatalities in China, Japan, and South Korea. Akin to other phleboviruses, SFTSV relies on a viral glycoprotein, Gc, to catalyze the merger of endosomal host and viral membranes during cell entry. Here, we describe the postfusion structure of SFTSV Gc, revealing that the molecular transformations the phleboviral Gc undergoes upon host cell entry are conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 67 publications
2
84
0
Order By: Relevance
“…The presence of plaques of different sizes cannot be explained at present. The crystal structure of the SFTSV Gc was recently reported, and it was shown to have some surface-exposed histidines that are important for triggering the pH-dependent entry process via glycoproteins (20). These findings indicate that several amino acids played critical roles in cell fusion and plaque formation.…”
Section: Discussionmentioning
confidence: 78%
“…The presence of plaques of different sizes cannot be explained at present. The crystal structure of the SFTSV Gc was recently reported, and it was shown to have some surface-exposed histidines that are important for triggering the pH-dependent entry process via glycoproteins (20). These findings indicate that several amino acids played critical roles in cell fusion and plaque formation.…”
Section: Discussionmentioning
confidence: 78%
“…Structural analysis of SFTSV and other phleboviruses demonstrated that Gc is a class II viral fusion protein and that the membrane fusion process is induced by structural rearrangement triggered by acidic conditions (2, 5,11,17). This fusion process could be evaluated as low-pH-dependent cell fusion caused by Gn and Gc expressed on the cell surface (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…De Boer et al reported that mutation of a single histidine (857H) in RVFV Gc completely abrogated virus entry as well as acid-induced Gc oligomerization (4). The histidine residue at position 940 (940H) of SFTSV Gc is also important for virus replication (11). Conversely, the structure and function of SFTSV Gn during virus entry remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations